The Role of Information Technology in Combating Hoaxes and Misinformation - Ronald Aloysius Romein; Glenny Chudra (Eduvest - Journal of Universal Studies, 2024)
Hoaxes and misinformation have become a serious problem in modern society, especially with the rapid development of information technology and social media. The spread of false information can cause great harm, both individually and socially, such as damaging reputation, causing panic, and disrupting social and political stability. This study aims to analyze the role of information technology in combating hoaxes and misinformation. This research uses qualitative research methods. The data collection technique in this research is a literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that information technology has an important role in combating hoaxes and misinformation. Social media platforms and technology companies can use various ways to combat hoaxes and misinformation, such as developing algorithms, verifying facts, working with fact-checking organizations, and providing education to users. However, it is important to remember that information technology is not the sole solution to combat hoaxes and misinformation. Joint efforts from various parties, such as the government, civil society, and academia, are needed to improve digital literacy and build a healthy information culture.